Regulating Crypto Assets: Understanding Stablecoins and Unbacked Crypto Assets Systemic Implication on the Financial Market - Jausyan, Maulana Ahmad Rayhan Al; Obed Juan Benito (The International Journal of Financial Systems, 2023)
To bring clarity to the emerging regulatory concerns, this study employs GARCH and TVP-VAR models to compare stablecoins and unbacked crypto assets' profiles and their systemic implications to the financial market. Using daily price data, it reveals that stablecoins are more stable than unbacked crypto assets while both are having weak connectivity at the same time. Moreover, stablecoins exert a more significant systemic impact on the financial market. The time-varying analysis also indicates high connectivity between crypto assets and traditional financial assets during crisis. These findings inform regulatory frameworks, ensuring stability in the financial system while promoting fintech innovation.